Resource Description and Access e il modello concettuale Records in Contexts. A Conceptual Model for Archival Description: oggetti comparabili? - Giorgia Di Marcantonio (JLIS.it, 2018)
After a methodological introduction and a recap of the evolutionary steps of the two descriptive models, the article aims at underlining contact points and differences between the Resource Description and Access (RDA) guidelines and the conceptual model Records in Contexts. A Conceptual Model for Archival Description (RiC-CM). The analysis is developed within the framework of the ongoing debate of the new descriptive models for cultural heritage, taking into account recent developments in integrated cultural systems.